A composite nanomaterial, its preparation method, and its application in the electrochemical detection of hyperoside.
Patent Information
- Application Number
- CN202611145964.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
AI Technical Summary
然而,传统电极对金丝桃苷的电化学响应较弱,电子传递效率低、氧化峰电流小,存在检测灵敏度低、选择性不强的问题
本发明提供了一种复合纳米材料的制备方法,包括以下步骤:步骤1、将水溶性金源、4-磺酰杯[4]芳烃、还原剂和水混合反应,得到pSC4-Au纳米粒子胶体溶液,其中pSC4指4-磺酰杯[4]芳烃;步骤2、将所述pSC4-Au纳米粒子胶体溶液和MESO-四(N-甲基-4-吡啶)卟啉五氯化铁(Ⅲ)溶液混合进行第一孵育,得到FeP-pSC4-Au纳米粒子自组装体复合液,其中FeP指MESO-四(N-甲基-4-吡啶)卟啉五氯化铁(Ⅲ);步骤3、将MXene溶液和MESO-四(N-甲基-4-吡啶)卟啉五氯化铁(Ⅲ)溶液混合进行第二孵育后,与所述FeP-pSC4-Au纳米粒子自组装体复合液混合进行第三孵育,得到所述复合纳米材料(记为MXene@FeP-pSC4-AuNPs)。
Smart Images

Figure CN122983148A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical technology, specifically relating to a composite nanomaterial, its preparation method, and its application in the electrochemical detection of hyperoside. Background Technology
[0002] Hyperoside, also known as quercetin-3- O β-Galactoside is a flavonol glycoside, a natural active ingredient widely found in various traditional Chinese medicines and medicinal and edible plants. Its molecular structure contains multiple phenolic hydroxyl groups, exhibiting various biological activities such as antioxidant, anti-inflammatory, cardiovascular protection, and neuroprotection. It holds significant research value in areas such as quality control of traditional Chinese medicine, development of natural drugs, and evaluation of functional foods.
[0003] Currently, the main methods for detecting hyperoside and other flavonoid glycosides include high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), ultraviolet-visible spectrophotometry (UV-Vis), fluorescence spectroscopy, chemiluminescence, electrochemiluminescence, and capillary electrophoresis. Among these, HPLC and LC-MS have high accuracy and separation capabilities, and are commonly used in the quantitative analysis of active ingredients in traditional Chinese medicine. However, these methods typically require expensive large-scale instruments, complex sample pretreatment processes, and specialized operators, resulting in lengthy detection procedures. They are not suitable for rapid screening in settings such as primary pharmacies, traditional Chinese medicine markets, and production and processing sites.
[0004] In recent years, electrochemical sensing technology has received widespread attention in the field of natural active small molecule detection due to its advantages such as instrument miniaturization, ease of operation, fast detection speed, low cost, and suitability for on-site testing. Hyperoside contains multiple electroactive phenolic hydroxyl groups, which can undergo redox reactions on the electrode surface, making it suitable for electrochemical detection. However, traditional electrodes exhibit weak electrochemical responses to hyperoside, with low electron transfer efficiency and small oxidation peak current, resulting in low detection sensitivity and poor selectivity. Especially in actual traditional Chinese medicine samples such as Cuscuta chinensis, complex matrices and structurally similar flavonoids may interfere with the detection results, further limiting the application of electrochemical detection methods. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a composite nanomaterial, its preparation method, and its application in the electrochemical detection of hyperoside. The graphite electrode modified with the composite nanomaterial prepared according to this invention for the electrochemical detection of hyperoside has the advantages of simple operation, fast detection speed, high sensitivity, good selectivity, and applicability to actual traditional Chinese medicine samples.
[0006] This invention provides a method for preparing composite nanomaterials, comprising the following steps: Step 1: Mix water-soluble gold source, 4-sulfonylcalix[4] aromatic hydrocarbon, reducing agent and water to obtain pSC4-Au nanoparticle colloidal solution, where pSC4 refers to 4-sulfonylcalix[4] aromatic hydrocarbon; Step 2: Mix the pSC4-Au nanoparticle colloidal solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a first incubation to obtain FeP-pSC4-Au nanoparticle self-assembled composite solution, wherein FeP refers to MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III); Step 3: After a second incubation, the MXene solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution are mixed and then mixed with the FeP-pSC4-Au nanoparticle self-assembled composite liquid for a third incubation to obtain the composite nanomaterial.
[0007] Preferably, the molar ratio of gold, 4-sulfonylcalix[4] aromatic hydrocarbon and reducing agent in the water-soluble gold source is 2~3:1:1, and the reducing agent includes NaBH4.
[0008] Preferably, the molar ratio of the water-soluble gold source to the volume of water is 0.4~0.6 mmol:1L.
[0009] Preferably, the volume ratio of the pSC4-Au nanoparticle colloidal solution and the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution in step 2 is 0.5~5:5~9.5, and the concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is 0.1 mmol / L.
[0010] Preferably, in step 3, the volume ratio of the MXene solution, the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution, and the FeP-pSC4-Au nanoparticle self-assembled composite solution is 1:1:1, the concentration of the MXene solution is 1 mg / mL, and the concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is 0.025~0.15 mmol / L.
[0011] The present invention also provides composite nanomaterials obtained by the preparation method described above, including MXene, and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III)-4-sulfonylcalix[4]arene-Au nanoparticle composite loaded on the surface of the MXene.
[0012] This invention also provides the application of the composite nanomaterials described in the above technical solution in the electrochemical detection of hyperoside.
[0013] The present invention also provides a sensor for the electrochemical detection of hyperoside, comprising a working electrode, a reference electrode and a counter electrode, wherein the working electrode is a modified graphite electrode, and the modified graphite electrode is a graphite electrode modified with the composite nanomaterial described in the above technical solution.
[0014] Preferably, the method for preparing the modified graphite electrode includes the following steps: drop-coating an MXene solution onto the surface of the graphite electrode and drying it; then drop-coating a MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution and performing a fourth incubation; drop-coating the FeP-pSC4-Au nanoparticle self-assembled composite liquid and performing a fifth incubation to obtain the modified graphite electrode.
[0015] This invention also provides a method for detecting the hyperoside content in traditional Chinese medicine using the sensor described above, comprising the following steps: The sample of the Chinese herbal medicine to be tested was extracted with an alcohol solution to obtain the test solution; The test solution was drop-coated onto the surface of the modified graphite electrode and incubated. The peak current was then measured, and the hyperoside content was obtained according to a predetermined standard curve.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for preparing composite nanomaterials, comprising the following steps: Step 1, mixing and reacting a water-soluble gold source, 4-sulfonylcalix[4]arene, a reducing agent and water to obtain a pSC4-Au nanoparticle colloidal solution, wherein pSC4 refers to 4-sulfonylcalix[4]arene; Step 2, mixing the pSC4-Au nanoparticle colloidal solution with a MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a first incubation to obtain FeP-pSC4- Au nanoparticle self-assembled composite liquid, wherein FeP refers to MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III); Step 3, after mixing MXene solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a second incubation, it is mixed with the FeP-pSC4-Au nanoparticle self-assembled composite liquid for a third incubation to obtain the composite nanomaterial (denoted as MXene@FeP-pSC4-AuNPs).
[0017] This invention uses MXene@FeP-pSC4-AuNPs composite nanomaterials to modify graphite electrodes for electrochemical detection of hyperoside. Among them, MXene can improve the electron transport efficiency of the electrode interface, AuNPs can increase the effective reaction area of the electrode, FeP (MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III)) can enhance the electrochemical response of hyperoside, and pSC4 (4-sulfonylcalix[4]arene) can improve the enrichment ability and selectivity of hyperoside through host-guest recognition. Compared with existing high performance liquid chromatography, fluorescence method and ordinary electrochemical detection method, the composite nanomaterial system designed in this invention can further overcome the shortcomings of single material conductivity, target molecule enrichment ability, interfacial catalytic performance and signal amplification ability. When used in conjunction with a portable electrochemical workstation, it can achieve efficient enrichment and electrochemical signal amplification of hyperoside. Therefore, this invention has the advantages of simple operation, fast detection speed, high detection sensitivity, strong specificity (selectivity) and applicability to actual Chinese medicine samples. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram illustrating the mechanism of hyperoside detection in this invention; Figure 2 The UV-Vis spectra of MXene, pSC4, FeP, pSC4-AuNPs, FeP-pSC4-AuNPs and MXene@FeP-pSC4-AuNPs are shown. Figure 3 In the diagram, A represents the DLS plots of MXene, FeP-pSC4-AuNPs, and MXene@FeP-pSC4-AuNPs, while B represents the Zeta-potential plots of MXene, pSC4-AuNPs, FeP-pSC4-AuNPs, MXene@FeP, and MXene@FeP-pSC4-AuNPs. Figure 4 In the image, A is the SEM image of MXene, B is the SEM image of FeP-pSC4-AuNPs, and C is the SEM image of MXene@FeP-pSC4-AuNPs. Figure 5 DPV of 1 μA hyperoside in 10 mM PBS buffer (pH 7.4) at different working electrodes; Figure 6Figure A shows the relationship between hyperoside concentration and peak current, and Figure B shows the relationship between the logarithm of hyperoside concentration and peak current. Figure 7 This is a bar chart showing the changes in oxidation peak current in the presence of metal ions and other organic compounds. Figure 8 Figure A shows the difference in peak current response of dodder seed samples from different origins in the electrochemical sensing system; Figure B is a comparison of the results of determining the hyperoside content in 6 dodder seed samples by the method of this invention and the high performance liquid chromatography (HPLC) method. Figure 9 Figure showing the results of time optimization for enriching hyperoside on modified electrodes; Figure 10 The figure shows the optimization results of different volume ratios of FeP solution and pSC4-AuNPs solution; Figure 11 The figure shows the optimized results of the FeP solution concentration. Detailed Implementation
[0020] This invention provides a method for preparing composite nanomaterials, comprising the following steps: Step 1: Mix water-soluble gold source, 4-sulfonylcalix[4] aromatic hydrocarbon, reducing agent and water to obtain pSC4-Au nanoparticle colloidal solution, where pSC4 refers to 4-sulfonylcalix[4] aromatic hydrocarbon; Step 2: Mix the pSC4-Au nanoparticle colloidal solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a first incubation to obtain FeP-pSC4-Au nanoparticle self-assembled composite solution, wherein FeP refers to MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III); Step 3: After mixing the MXene solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a second incubation, the mixture is then mixed with the FeP-pSC4-Au nanoparticle self-assembled composite liquid for a third incubation to obtain the composite nanomaterial (denoted as MXene@FeP-pSC4-AuNPs).
[0021] Unless otherwise specified, all materials and equipment used in this invention are commercially available products in the field.
[0022] Step 1: In this invention, water-soluble gold source, 4-sulfonylcalix[4] aromatic hydrocarbon, reducing agent and water are mixed and reacted to obtain pSC4-Au nanoparticles.
[0023] In this invention, the water-soluble gold source preferably includes HAuCl4.
[0024] In this invention, the CAS number of the 4-sulfonylcalix[4]aromatic hydrocarbon (pSC4) is 112269-92-8. The molar ratio of gold to 4-sulfonylcalix[4]aromatic hydrocarbon in the water-soluble gold source is preferably 2~3:1, specifically 2.5:1 or 2.63:1.
[0025] In this invention, the reducing agent preferably includes NaBH4. The molar ratio of gold to reducing agent in the water-soluble gold source is preferably 2~3:1, specifically 2.5:1 or 2.63:1.
[0026] In this invention, the molar ratio of the gold source, 4-sulfonylcalix[4] aromatic hydrocarbon and reducing agent in the water-soluble gold source is preferably 2~3:1:1, specifically 2.63:1:1.
[0027] In this invention, the preferred molar ratio of the water-soluble gold source to the volume of water is 0.4~0.6 mmol:1 L; in this embodiment, it is specifically 5.26 × 10⁻⁶ mmol / L. -2 mmol:100mL.
[0028] In this invention, the preferred method for mixing the water-soluble gold source, 4-sulfonylcalix[4] aromatic hydrocarbon, reducing agent, and water is as follows: first, the water-soluble gold source solution and the 4-sulfonylcalix[4] aromatic hydrocarbon solution are stirred for the first time, and then the reducing agent solution is added for the second stirring. The first stirring is preferably carried out at room temperature (10~30℃) and in the dark, and the preferred time is 20 min; during the first stirring, the water-soluble gold source (AuCl4) is stirred for the second time. - The 4-sulfonylcalix[4] aromatic hydrocarbon molecules are in full contact with the gold precursor. The 4-sulfonylcalix[4] aromatic hydrocarbon molecules interact with the gold precursor through electrostatic interaction, coordination interaction and host-guest recognition through sulfonic acid group, phenolic hydroxyl group and calixarene cavity structure, forming a uniform pre-assembled system, which provides an environment for the subsequent reduction and stable growth of gold nanoparticles. The second stirring is preferably carried out at room temperature (10~30℃) and in the dark, and the time is preferably 2h. During the second stirring process, the reducing agent reduces Au(III) in the water-soluble gold source to Au(0), and Au(0) further undergoes rapid nucleation and gradually grows to form gold nanoparticles. At the same time, the 4-sulfonylcalix[4] aromatic hydrocarbon is adsorbed or coated on the surface of the gold nanoparticles, and inhibits the aggregation of gold nanoparticles through steric hindrance, electrostatic repulsion and host-guest recognition, thereby obtaining 4-sulfonylcalix[4] aromatic hydrocarbon-gold nanoparticles with uniform particle size and good dispersibility.
[0029] After obtaining pSC4-Au nanoparticles, the present invention mixes the pSC4-Au nanoparticle colloidal solution with MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a first incubation to obtain FeP-pSC4-Au nanoparticle self-assembled composite liquid, wherein FeP refers to MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III).
[0030] In this invention, the CAS number of MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) (FeP) in the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) (FeP) solution is 133314-07-5.
[0031] In this invention, the volume ratio of the pSC4-Au nanoparticle colloidal solution and the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution in step 2 is preferably 0.5~5:5~9.5, specifically 0.5:9.5, 1.0:9.0, 2.0:8.0 or 5.0:5.0 (1:1); the concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is preferably 0.1 mmol / L.
[0032] In this invention, the first incubation is preferably carried out at room temperature (10~30℃) for a time of 20~40 min, specifically 30 min. During the first incubation, pSC4-Au nanoparticles self-assemble with FeP.
[0033] After obtaining the FeP-pSC4-Au nanoparticle self-assembled composite liquid, the present invention mixes MXene solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a second incubation, and then mixes it with the FeP-pSC4-Au nanoparticle self-assembled composite liquid for a third incubation to obtain the composite nanomaterial (denoted as MXene@FeP-pSC4-AuNPs).
[0034] In this invention, the volume ratio of the MXene solution, MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution, and FeP-pSC4-Au nanoparticle self-assembled composite solution in step 3 is preferably 1:1:1. The concentration of the MXene solution is preferably 1 mg / mL, and the concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is preferably 0.025~0.15 mmol / L, specifically 0.025, 0.05, 0.1, or 0.15 mmol / L. The porphyrin ring structure of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) facilitates stable interaction with MXene and pSC4-Au nanoparticles. The central Fe(III) site can improve interfacial electron transfer and electrochemical catalytic activity, and synergistically enhance the selective response to target molecules with the host-guest recognition effect of pSC4-Au nanoparticles.
[0035] In this invention, both the second and third incubations are preferably carried out at room temperature (10~30℃), and the time is independently preferably 20~40 min, specifically 30 min. During the second and third incubation processes, FeP-pSC4-Au nanoparticle self-assemblies, MXene, and FeP form composite nanomaterials.
[0036] The present invention also provides composite nanomaterials obtained by the preparation method described above, including MXene, and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric(III)-4-sulfonylcalix[4]arene-Au nanoparticle complex (i.e. FeP-pSC4-AuNPs self-assembly) loaded on the surface of the MXene.
[0037] This invention also provides the application of the composite nanomaterials described in the above technical solution in the electrochemical detection of hyperoside.
[0038] The present invention also provides a sensor for the electrochemical detection of hyperoside, comprising a working electrode, a reference electrode and a counter electrode, wherein the working electrode is a modified graphite electrode, and the modified graphite electrode is a graphite electrode modified with the composite nanomaterial described in the above technical solution.
[0039] In this invention, the preparation method of the modified graphite electrode includes the following steps: drop-coating MXene solution onto the surface of the graphite electrode and drying it; then drop-coating MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution and performing a fourth incubation; drop-coating the FeP-pSC4-Au nanoparticle self-assembled composite liquid and performing a fifth incubation to obtain the modified graphite electrode.
[0040] In this invention, the graphite electrode is preferably pretreated before use. The pretreatment is preferably performed by polishing and cleaning in sequence. The polishing is preferably performed using 0.05μm alumina powder. The cleaning is preferably performed by ultrasonic cleaning with deionized water, anhydrous ethanol and deionized water in sequence.
[0041] In this invention, the concentration of the MXene solution is preferably 1 mg / mL; the first drying temperature is preferably 50°C, and the drying time is preferably until constant weight is achieved. The concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is preferably 0.1 mmol / L; the fourth incubation is preferably carried out at room temperature, and the incubation time is preferably 30 min. The FeP-pSC4-Au nanoparticle self-assembled composite solution is the FeP-pSC4-Au nanoparticle self-assembled composite solution obtained in step 2, and the volume ratio of the MXene solution, the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution, and the FeP-pSC4-Au nanoparticle self-assembled composite solution is preferably 1:1:1; the fifth incubation is preferably carried out at room temperature, and the incubation time is preferably 30 min.
[0042] In this embodiment of the invention, the diameter of the graphite electrode is preferably 3 mm, and the drop volume of the MXene solution, the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution, and the FeP-pSC4-Au nanoparticle self-assembled composite liquid is 30 μL.
[0043] This invention modifies the surface of the graphite electrode to ensure that the materials used in each step are modified at the corresponding positions, which is beneficial to the stability of electrochemical detection.
[0044] This invention also provides a method for detecting the hyperoside content in traditional Chinese medicine using the sensor described above, comprising the following steps: The sample of the Chinese herbal medicine to be tested was extracted with an alcohol solution to obtain the test solution; The test solution was drop-coated onto the surface of the modified graphite electrode and incubated. The peak current was then measured, and the hyperoside content was obtained according to a predetermined standard curve.
[0045] In this invention, the herbal medicine to be tested preferably includes Cuscuta chinensis, which is preferably pulverized before extraction. The alcohol solution is preferably an aqueous methanol solution, wherein the volume fraction of methanol in the aqueous methanol solution is preferably 80%; the volume ratio of the herbal medicine sample to the alcohol solution is preferably 1g:40mL. The extraction is preferably performed under ultrasound, wherein the frequency of ultrasound is preferably 40kHz, and the time is preferably 1h.
[0046] This invention does not have special requirements for the drop volume of the test solution, as long as it completely covers the electrode. The incubation time is preferably 30~120 min, specifically 30 min, 60 min, 90 min or 120 min. The linear range of the standard curve is preferably 1 nmol / L~0.1 μmol / L.
[0047] In this invention, the modified graphite electrode is preferably used as the working electrode, the calomel electrode as the reference electrode, and the platinum wire electrode as the counter electrode, forming a three-electrode system. The signal of hyperoside in the target traditional Chinese medicine is collected using differential pulse voltammetry (DPV): within a range of 100 mV to 800 mV and in 10 mM PBS buffer (pH 7.4), hyperoside is electrochemically detected using a graphite electrode modified with MXene@FeP-pSC4-AuNPs composite nanomaterials (DPV parameters set as follows: pulse amplitude 0.04 V, pulse width 40 ms, pulse period 100 ms, sampling width 10 ms).
[0048] Hypericin is a flavonoid glycoside. The modified graphite electrode of the sensor described in this invention can specifically bind to the target analyte hypericin, while flavonoid compounds with similar structures to hypericin, such as quercetin, have little interference with it.
[0049] Figure 1 This diagram illustrates the mechanism for detecting hyperin in this invention. An MXene@FeP-pSC4-AuNPs composite nanomaterial was constructed: MXene@FeP and FeP-pSC4-AuNPs composite materials were prepared separately, and then further assembled to form an MXene@FeP-pSC4-AuNPs multi-component composite nanomaterial. This invention uses a drop-coating method to modify the MXene@FeP-pSC4-AuNPs composite material onto the electrode surface, forming a stable functionalized sensing interface for the electrochemical detection of hyperin.
[0050] To further illustrate the present invention, the composite nanomaterials provided by the present invention, their preparation methods, and their application in the electrochemical detection of hyperoside are described in detail below with reference to the accompanying drawings and embodiments. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0051] Example 1 The preparation method of MXene@FeP-pSC4-AuNPs composite nanomaterials includes the following steps: (1) Synthesis of pSC4-AuNPs, the specific process is as follows: HAuCl4 solution (2 mL, 2.63 × 10⁻⁶) was prepared. -2 mol / L) and pSC4 (4-sulfonylcalix[4]aromatic) solution (2 mL, 10 -2Mix the NaBH4 solution (mol / L) at room temperature and add water to 100 mL. Stir for 20 min in the dark, then immediately add 2 mL of freshly prepared NaBH4 solution (10 mol / L). -2 (mol / L), and then stirred for 2 h under the same conditions. When the solution color gradually changes from yellow to brown, and finally to reddish-brown, the preparation is complete. The synthesized pSC4-AuNPs colloidal solution was stored in a brown bottle at 4°C.
[0052] (2) Preparation of FeP-pSC4-AuNPs: The specific process is as follows: 100 μL of FeP (MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III)) solution (0.1 mM) is mixed with 900 μL of pSC4-AuNPs colloidal solution obtained in step (1) and incubated for 30 min to prepare FeP-pSC4-AuNPs self-assembled composite solution.
[0053] (3) Preparation of MXene@FeP-pSC4-AuNPs: Weigh 3 mg of MXene and add 3 mL of ultrapure water. Sonicate in an ice bath for 40 min to prepare a 1 mg / mL MXene solution. Take 200 μL of MXene solution, add 200 μL of FeP (0.1 mM) and incubate for 30 min. Then mix with 200 μL of FeP-pSC4-AuNPs self-assembled composite solution obtained in step (2) and incubate for 30 min to prepare an MXene@FeP-pSC4-AuNPs composite nanomaterial suspension. Freeze-dry to obtain MXene@FeP-pSC4-AuNPs composite nanomaterial.
[0054] Example 2 The preparation of the MXene@FeP-pSC4-AuNPs composite nanomaterial modified electrode involved the following process: A graphite electrode (GE, 3 mm in diameter) was polished with 0.05 μm alumina powder until the surface was smooth. The polished GE was then subjected to ultrasonic treatment sequentially in deionized water, anhydrous ethanol, and DW.
[0055] Subsequently, 3 mg of MXene was weighed and added to 3 mL of ultrapure water, and sonicated in an ice bath for 40 min to prepare a 1 mg / mL MXene solution; 30 μL of MXene solution was dropped onto the GE surface and dried in a 50℃ oven until the surface was completely dry; then 30 μL of FeP (0.1 mM) solution was dropped onto the above electrode surface and incubated at room temperature for 30 min; finally, 30 μL of the FeP-pSC4-AuNPs composite solution prepared in step (2) of Example 1 was dropped onto the surface and incubated at room temperature for 30 min to prepare an MXene@FeP-pSC4-AuNPs modified graphite electrode.
[0056] Test Example 1: Characterization of MXene@FeP-pSC4-AuNPs composite nanomaterials The MXene@FeP-pSC4-AuNPs composite nanomaterials were characterized using UV-Vis, Zeta-potential, DLS, and SEM techniques. The experimental conditions for UV-Vis spectroscopy were as follows: scanning wavelength range: 200–700 nm; scanning speed: normal; scanning interval: 1 nm.
[0057] Figure 2 The UV-Vis spectra of MXene, pSC4, FeP, pSC4-AuNPs, FeP-pSC4-AuNPs, and MXene@FeP-pSC4-AuNPs are shown.
[0058] like Figure 2 As shown, the characteristic absorption peak of pSC4 is located at 280 nm, and pSC4-AuNPs have peaks at both 280 nm and 537 nm, proving the successful binding of pSC4-AuNPs. The characteristic absorption peak of FeP is located at 422 nm. After self-assembly with pSC4-AuNPs, the characteristic absorption peak blue-shifts to 520 nm, and the FeP absorption peak blue-shifts to 406 nm, indicating the successful formation of FeP-pSC4-AuNPs through self-assembly. MXene has absorption at 280 nm. When FeP-pSC4-AuNPs are mixed with MXene, although the intensity of the characteristic absorption signals of each component changes due to the introduction of MXene, they are still clearly identifiable, further confirming the successful construction of the MXene@FeP-pSC4-AuNPs composite nanomaterial.
[0059] To investigate the microscopic size characteristics and surface charge properties of various materials and to verify the successful preparation of composite materials, the particle size and zeta potential of different samples were tested and analyzed. Figure 3 In Figure A, the DLS diagrams of MXene, FeP-pSC4-AuNPs and MXene@FeP-pSC4-AuNPs are shown. In Figure B, the Zeta-potential diagrams of MXene, pSC4-AuNPs, FeP-pSC4-AuNPs, MXene@FeP and MXene@FeP-pSC4-AuNPs are shown. The preparation method of MXene@FeP is as described in step (3) of Example 1.
[0060] Figure 3Figure A shows the particle sizes of MXene, FeP-pSC4-AuNPs, and MXene@FeP-pSC4-AuNPs. MXene exhibits a particle size of approximately 490 nm, while FeP-pSC4-AuNPs exhibit a smaller particle size of approximately 120 nm. However, after loading FeP-pSC4-AuNPs onto MXene, the particle size of the system significantly increases to approximately 650 nm, directly demonstrating that the FeP-pSC4-AuNPs nanocomposite was successfully loaded onto the MXene surface. Figure 3 Figure B shows the Zeta potential diagrams for various materials. As can be seen from the figure, the potential of pSC4-AuNPs is -24 mV, while that of FeP-pSC4-AuNPs is -11 mV. The significantly higher potential of FeP-pSC4-AuNPs indicates successful self-assembly of FeP-pSC4-AuNPs. MXene has a potential of -18 mV, while MXene@FeP has a potential of -2 mV, indicating that positively charged FeP has successfully adsorbed onto the negatively charged MXene surface, achieving material composite. Finally, the composite material MXene@FeP-pSC4-AuNPs has a potential of -16 mV, significantly lower than that of MXene@FeP, proving the successful synthesis of the MXene@FeP-pSC4-AuNPs composite nanomaterial.
[0061] Figure 4 In the image, A is the SEM image of MXene, B is the SEM image of FeP-pSC4-AuNPs, and C is the SEM image of MXene@FeP-pSC4-AuNPs.
[0062] Figure 4 The image shows SEM images of MXene, FeP-pSC4-AuNPs, and MXene@FeP-pSC4-AuNPs composite nanomaterials. Figure 4 The image in section A reflects the overall appearance of MXene, indicating that MXene exhibits a typical two-dimensional accordion-like layered structure with clear edge edges, natural wrinkles on the surface, and distinct interlayer gaps. Figure 4 In the B-cell matrix, FeP-pSC4-AuNPs exhibit a spherical structure with chain-like structures between the spherical particles, indicating that FeP-pSC4-AuNPs successfully self-assembled. Figure 4 The C-value indicates that a large number of FeP-pSC4-AuNPs self-assembled composite nanoparticles are uniformly loaded on the surface of the MXene sheets, and the particle size is calculated to be around 600 nm according to the scale bar, which is consistent with the DLS results. This indicates that the MXene@FeP-pSC4-AuNPs composite nanomaterial has been successfully synthesized.
[0063] This invention employs scanning electron microscopy, ultraviolet-visible absorption spectroscopy, and zeta potential to systematically analyze the morphology, optical absorption characteristics, and surface charge changes of the material. By comparing the morphological differences, characteristic absorption peak changes, and potential changes before and after the composite of different components, the effective combination between the functional components is verified, demonstrating the successful construction of the MXene@FeP-pSC4-AuNPs composite material.
[0064] Test Example 2: Feasibility Verification of MXene@FeP-pSC4-AuNPs Composite Nanomaterials To verify the feasibility of using MXene@FeP-pSC4-AuNPs composite nanomaterials as electrode modification materials for hyperoside detection, graphite electrodes (GE) with different modification states were prepared, and their electrochemical behavior and hyperoside response signals were compared and analyzed.
[0065] First, the bare graphite electrodes were modified with different nanomaterials to obtain bare graphite electrodes (GE), MXene / GE, FeP / GE, pSC4-AuNPs / GE, MXene@FeP / GE, MXene@pSC4-AuNPs / GE, FeP-pSC4-AuNPs / GE and MXene@FeP-pSC4-AuNPs / GE (the modification of the MXene@FeP-pSC4-AuNPs / GE composite nanomaterial is as described in Example 2; the other control electrodes maintained the same electrode pretreatment, drop-coating volume and incubation conditions, only the combination of modification materials was changed).
[0066] Using potassium ferricyanide / potassium ferrocyanide solution as an electrochemical probe, cyclic voltammetry was employed to characterize different modified electrodes. The test conditions were as follows: a modified graphite electrode was used as the working electrode, a calomel electrode as the reference electrode, and a platinum wire electrode as the counter electrode. Cyclic voltammetry was performed in a 5 mM potassium ferricyanide / potassium ferrocyanide solution, with a potential range of 100 mV to 800 mV, a scan rate of 100 mV / s, and 2 scan cycles.
[0067] Figure 5 The DPV of 1 μM hyperoside in 10 mM PBS buffer (pH 7.4) on different working electrodes.
[0068] like Figure 5As shown, the hyperoside peak current of FeP-pSC4-AuNPs / GE is at -17 μA, while that of MXene@pSC4-AuNPs / GE is at -16 μA, showing only slight variations. However, the hyperoside peak current of MXene@FeP-pSC4-AuNPs / GE is at -100 μA, indicating a significantly enhanced electrochemical signal. This result demonstrates a significant synergistic effect among the components of MXene@FeP-pSC4-AuNPs, achieving highly specific capture of the target hyperoside and validating the feasibility of the experiment.
[0069] This invention utilizes cyclic voltammetry (CV) to electrochemically characterize electrodes at different modification stages, examining changes in the electron transport capacity at the electrode interface to determine whether the composite material has been successfully immobilized on the electrode surface. The modified electrode effectively improves the charge transport efficiency at the electrode interface, providing a sound electrochemical basis for the subsequent sensitive detection of hyperoside.
[0070] Test Example 3: Quantitative Analysis of Hyperoside To verify the quantitative detection capability of hyperoside, a graphite electrode modified with MXene@FeP-pSC4-AuNPs composite nanomaterial was used as the working electrode. Differential pulse voltammetry was used to detect hyperoside standard solutions of different concentrations. The modified graphite electrode was used as the working electrode, the calomel electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode.
[0071] Figure 6 In diagram A, the relationship between hyperoside concentration and peak current is shown (hyperoside concentrations are: 0.001 μM, 0.0025 μM, 0.005 μM, 0.01 μM, 0.03 μM, 0.05 μM, 0.1 μM), and in diagram B, the relationship between the logarithm of hyperoside concentration and peak current is shown. Figure 6 As shown, within the concentration range of 1 nM to 0.10 μM, the peak current of the sensor exhibited a significant increasing trend with the gradual increase of the hyperoside standard solution concentration, while the peak potential remained stable without significant shift. To further quantify the correlation between hyperoside concentration and peak current, [further details are needed]. Figure 6 Linear fitting analysis was performed on the experimental data of A. For example... Figure 6 As shown in Figure B, the absolute value of the peak current of hyperoside oxidation exhibits a good linear relationship with the logarithm of hyperoside concentration. The fitted linear regression equation is I = 444.99 lgC + 138.41 μA, and the correlation coefficient R0 is [value missing]. 2 =0.9932.
[0072] The electrochemical sensor constructed in this invention has a detection limit as low as 0.2795 nM, which is significantly lower than that of previously reported hyperoside detection methods (chemiluminescence, fluorescence spectroscopy, electrochemiluminescence, etc.), and exhibits superior detection sensitivity.
[0073] This invention involves dropwise adding hyperoside solutions of different concentrations to the surface of a modified electrode, allowing it to recognize and accumulate at the pSC4 functional interface. Subsequently, differential pulse voltammetry (DPV) is used to quantitatively detect the different concentrations of hyperoside. By analyzing the relationship between hyperoside concentration and peak current, a quantitative detection standard curve is established, and analytical performance parameters such as the detection limit and linear range are calculated to evaluate the sensitivity of this sensing platform for hyperoside detection.
[0074] Test Example 4: Specificity of the Hyperoside Sensor To evaluate the specificity of the sensor, quercetin, leucine, and common metal ions (CaCl2, ZnSO4) from Cuscuta chinensis, which have structures similar to hyperoside, were selected as interfering substances (2×10⁻⁶). -5 M), its electrochemical response was tested under the same experimental conditions, and compared with the target 2×10 -7 The responses of hyperoside M were compared.
[0075] Figure 7 This is a bar chart showing the changes in oxidation peak current in the presence of metal ions and other organic compounds.
[0076] like Figure 7 As shown, the oxidation peak current of the target analyte, hyperoside, reached as high as 98 μA, exhibiting an extremely strong electrochemical response. The response peak currents of all interfering substances were significantly lower than those of the target analyte: quercetin approximately 9 μA, leucine approximately 15 μA, CaCl2 approximately 7 μA, ZnSO4 approximately 6 μA, and the blank group response approximately 3 μA, close to the baseline level. This indicates that the sensor of this invention can only specifically bind to the target analyte, hyperoside, thereby generating a significant current response, while interfering substances cannot bind and only produce a weak background signal. This also verifies that the sensor of this invention has the potential to be applied to the detection of hyperoside in real samples of Cuscuta chinensis.
[0077] This invention examines the selectivity and detection capability of a sensor in actual samples. Due to the complex composition of traditional Chinese medicine (TCM) sample systems, which may contain various structurally similar or electroactive interfering substances, it is necessary to evaluate the sensor's ability to recognize hyperoside through specificity experiments. This invention introduces common interfering substances or structural analogs and compares their effects on the electrochemical response signal, verifying that the MXene@FeP-pSC4-AuNPs modified electrode exhibits good selectivity for hyperoside. Based on this, the sensor is further applied to the detection of hyperoside in actual Cuscuta chinensis samples to verify the feasibility and application potential of the method in the rapid detection of active ingredients in TCM.
[0078] Test Example 5: Feasibility of Clinical Detection of Hyperoside Six groups of dodder seed samples from different origins were weighed (30g each) and pulverized. First, coarse grinding was performed using a pulverizer, followed by fine grinding using a mortar and pestle. The pulverized particles were then sieved. One g of the sample was placed in a 50mL volumetric flask, and 40mL of 80% methanol solution was added. The flask was sonicated at 40kHz for 1 hour. After cooling, the volume was adjusted to the mark with 80% methanol solution, and the mixture was shaken well. The solution was then filtered through a 0.22μm filter membrane into a vial for analysis.
[0079] Figure 8 In Figure A, the peak current response of six groups of dodder samples from different origins in the electrochemical sensing system is shown. There are certain differences in peak current among the different samples. Figure 8 The results of the method of the present invention were compared with those of the traditional high performance liquid chromatography (HPLC) method (Determination of Cuscuta chinensis content in medicinal materials and processed slices in Part I of the Chinese Pharmacopoeia 2025 and 0512 HPLC method in Part IV). The data showed that the two methods were highly consistent in the determination results of 6 groups of samples, with no significant difference, indicating that the method of the present invention has the same accuracy as HPLC in actual sample detection.
[0080] To achieve optimal detection performance, this invention focuses on investigating the effects of key factors such as hyperoside enrichment time, the composite ratio of FeP and pSC4-AuNPs, and FeP concentration on the electrochemical response signal. By comparing the changes in the hyperoside oxidation peak current under different experimental conditions, the optimal experimental parameters were selected. This optimization process helps improve the enrichment efficiency of the target molecule on the electrode surface, enhances the electrochemical signal response, and improves the stability and repeatability of the sensor detection.
[0081] Example 3: Optimization of Experimental Conditions 1. Optimization of hyperoside enrichment time on the electrode The enrichment time of hyperoside on the electrode was optimized, and the effect of different incubation times (0 min, 30 min, 60 min, 90 min, 120 min) on the peak current of the sensor response was investigated. The results are as follows: Figure 9 As shown in the figure. Considering both detection efficiency and response sensitivity, 90 min was selected as the optimal enrichment time for hyperoside.
[0082] 2. Optimization of the ratio of FeP to pSC4-AuNPs To determine the optimal mixing ratio of FeP to pSC4-AuNPs, the effects of different volume ratios of FeP solution to pSC4-AuNPs colloidal solution (0.5:9.5, 1.0:9.0, 2.0:8.0, 5.0:5.0) on the peak current of the sensor's electrochemical response were systematically investigated. The results are as follows: Figure 10 As shown.
[0083] When the volume ratio of FeP solution to pSC4-AuNPs solution was 0.5:9.5, 2.0:8.0, and 5.0:5.0, the oxidation peak current of hyperoside by the sensor was relatively small. However, when the volume ratio was 1.0:9.0, the oxidation peak current of hyperoside by the sensor reached its maximum value (approximately 78 μA), indicating that this ratio achieves optimal synergy between FeP and pSC4-AuNPs, resulting in the highest electrochemical response signal. Based on the experimental results, 1.0:9.0 (v / v) was selected as the optimal mixing ratio of FeP and pSC4-AuNPs, providing the optimal interface construction conditions for the sensor's high-sensitivity detection.
[0084] 3. Optimization of FeP concentration To optimize the FeP concentration of the modified electrode, the effect of different FeP concentrations (0.025, 0.05, 0.1, and 0.15 mM) on the peak current of the sensor's electrochemical response was systematically investigated. The results are as follows: Figure 11 As shown.
[0085] Taking into account both the sensor's response sensitivity and the range of its electrochemical response peaks, 0.1 mM was selected as the optimal working concentration of FeP to achieve the maximum capture efficiency and highest response signal for hyperoside.
[0086] The method of the present invention is compared with existing common methods for the detection of hyperoside, as shown in Table 1. The detection method of the present invention has a lower detection limit.
[0087] Table 1. Comparison of the hyperoside detection method based on MXene@FeP-pSC4-AuNPs composite nanomaterials of the present invention with existing technologies.
[0088] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on the present invention without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing composite nanomaterials, characterized in that, Includes the following steps: Step 1: Mix water-soluble gold source, 4-sulfonylcalix[4] aromatic hydrocarbon, reducing agent and water to obtain pSC4-Au nanoparticle colloidal solution, where pSC4 refers to 4-sulfonylcalix[4] aromatic hydrocarbon; Step 2: Mix the pSC4-Au nanoparticle colloidal solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution for a first incubation to obtain FeP-pSC4-Au nanoparticle self-assembled composite solution, wherein FeP refers to MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III); Step 3: After a second incubation, the MXene solution and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution are mixed and then mixed with the FeP-pSC4-Au nanoparticle self-assembled composite liquid for a third incubation to obtain the composite nanomaterial.
2. The preparation method according to claim 1, characterized in that, The molar ratio of gold, 4-sulfonylcalix[4] aromatic hydrocarbon and reducing agent in the water-soluble gold source is 2~3:1:1, and the reducing agent includes NaBH4.
3. The preparation method according to claim 1 or 2, characterized in that, The molar ratio of the water-soluble gold source to the volume of water is 0.4~0.6 mmol:1L.
4. The preparation method according to claim 3, characterized in that, In step 2, the volume ratio of the pSC4-Au nanoparticle colloidal solution to the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is 0.5~5:5~9.5, and the concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is 0.1 mmol / L.
5. The preparation method according to claim 4, characterized in that, In step 3, the volume ratio of the MXene solution, the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution, and the FeP-pSC4-Au nanoparticle self-assembled composite solution is 1:1:
1. The concentration of the MXene solution is 1 mg / mL, and the concentration of the MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution is 0.025~0.15 mmol / L.
6. The composite nanomaterial obtained by the preparation method according to any one of claims 1 to 5, characterized in that, Including MXene, and MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III)-4-sulfonyl calix [4] aromatic-Au nanoparticle complex loaded on the surface of the MXene.
7. The application of the composite nanomaterial according to claim 6 in the electrochemical detection of hyperoside.
8. A sensor for electrochemical detection of hyperoside, comprising a working electrode, a reference electrode and a counter electrode, wherein the working electrode is a modified graphite electrode, and the modified graphite electrode is a graphite electrode modified with the composite nanomaterial of claim 6.
9. The sensor according to claim 8, characterized in that, The method for preparing the modified graphite electrode includes the following steps: drop-coating an MXene solution onto the surface of the graphite electrode and drying it; then drop-coating a MESO-tetra(N-methyl-4-pyridine)porphyrin ferric chloride (III) solution and performing a fourth incubation; drop-coating the FeP-pSC4-Au nanoparticle self-assembled composite liquid and performing a fifth incubation to obtain the modified graphite electrode.
10. A method for detecting the hyperoside content in traditional Chinese medicine using the sensor described in claim 8 or 9, comprising the following steps: The sample of the Chinese herbal medicine to be tested was extracted with an alcohol solution to obtain the test solution; The test solution was drop-coated onto the surface of the modified graphite electrode and incubated. The peak current was then measured, and the hyperoside content was obtained according to a predetermined standard curve.